Nck adaptor proteins modulate differentiation and effector function of T cells. Issue 3 (20th May 2015) - Lu, Kun‐Hui; Keppler, Selina; Leithäuser, Frank; Mattfeldt, Torsten; Castello, Angelo; Kostezka, Ulrike; Küblbeck, Günter; Schmitt, Sabine; Klevenz, Alexandra; Prokosch, Sandra; Pougialis, Georg; Pawson, Tony; et al.
Abstract : Loss of Nck proteins in T cells impairs germinal center formation, Tfh cell survival, cytokine production, and T cell‐dependent antibody responses. Abstract : Understanding the molecular mechanisms regulating T cell reactivity is required for successful reprogramming of immune responses in medical conditions, characterized by dysfunctions of the immune system. Nck proteins are cytoplasmic adaptors mediating diverse cellular functions, including TCR signaling. By enhancing TCR signal strength, Nck proteins influence thymic selection and regulate the size and sensitivity of the peripheral T cell repertoire. Here, we investigated the contribution of Nck proteins to CD4 + T cell differentiation and effector function using Nck.T −/− mice. Impaired GC formation and reduced Tfh were observed in Nck.T −/− mice after immunization with T cell‐dependent antigens. Th2/Tfh‐related cytokines, such as IL‐4, IL‐10, and IL‐21, were decreased in Nck.T −/− mice T cells. Moreover, an increased susceptibility to cell death of Tfh cells in Nck.T −/− mice was associated with decreased levels of Akt phosphorylation. As a result of this dysregulation in Tfh cells of Nck.T −/− mice, we found impaired production and affinity maturation of antibodies against T cell‐dependent antigens. Thus, Nck proteins not only participate in thymic selection and generation of the peripheral T cell repertoire but also are involved in the differentiation and effector functions of CD4 + T cells.